2015
DOI: 10.1108/imr-03-2014-0091
|View full text |Cite
|
Sign up to set email alerts
|

Consumer perceptions of CSR: (how) is China different?

Abstract: Purpose -Most studies on consumers and CSR have focused on Western contexts. Consequently, good insight is lacking into non-Western markets where consumers may respond differently. China is a case in point, despite the popularity of the CSR concept and high societal expectations of firms. This article examines how Chinese consumers perceive the underlying components of CSR found in Western countries; whether their CSR expectations differ for local Chinese compared to foreign firms; and whether results differ a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 48 publications
(92 reference statements)
1
27
0
1
Order By: Relevance
“…Thus, the impact of CSR in developing nations has remained largely unexplored. In fact, Kolk et al (2015) established that constructs developed in the West are not applicable the same way in China, and suggested that there is a need to focus on non-Western countries.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the impact of CSR in developing nations has remained largely unexplored. In fact, Kolk et al (2015) established that constructs developed in the West are not applicable the same way in China, and suggested that there is a need to focus on non-Western countries.…”
Section: Introductionmentioning
confidence: 99%
“…Namely, comparing to their counterparts in the middle and western regions of China, firms in eastern regions enjoy more benefits in M&A performance by fulfilling CSR. Compared to other studies that focus on CSR differences across regions [42][43][44], this paper further explores different CSR-performance linkages across regions. Our study indicates that different markets, legal requirements, and governance environments might have significant effects on CSR-performance linkages.…”
Section: Discussionmentioning
confidence: 99%
“…Kühn found that, unlike companies in Western countries, African companies' CSR activities mainly focus on philanthropy, and CSR reporting was positively influenced by both GDP and the level of governance standards. Kolk et al (2015) [43] conducted a survey in China and found that Chinese customers perceive two components (instead of four) in Western CSR constructs. Baughn et al (2007) [44] conducted a survey in 104 countries and found that CSR is different across countries and regions.…”
Section: Csr Geographical Regions and Long-term Manda Performancementioning
confidence: 99%
“…Therefore, the standards that apply to CSR and people's perceptions regarding CSR differ for each country. So far most studies concerning CSR have been conducted in USA or the UK, and limited studies have considered countries with different social and cultural environments [37]. Therefore, it is valuable to study different countries for the generalization of findings of CSR studies [38].…”
Section: Difference Of China and Korea In Effect Of Csr On Organizatimentioning
confidence: 99%